2009
DOI: 10.1158/1535-7163.mct-08-1016
|View full text |Cite
|
Sign up to set email alerts
|

Blood flow and Vd (water): both biomarkers required for interpreting the effects of vascular targeting agents on tumor and normal tissue

Abstract: Positron emission tomography studies with oxygen-15 -labeled water provide in vivo quantitative tissue perfusion variables-blood flow and fractional volume of distribution of water [V d (water)]. To investigate the relationship between perfusion variables and the effect of vasculartargeting agents on vasculature, we measured tissue perfusion in tumors, spleen, kidney, and liver before and after treatment with combretastatin-A4-phosphate, a combination of nicotinamide and carbogen (N/C), and interferon (IFN). W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…30,31) In conclusion, based on the present study we propose that radiolabeled glycerol could be used as a molecular probe targeting agAQPs. This might enable the estimation of agAQP expression by comparing radioactivity in the tissue of interest and plasma in the same individual, thus providing valuable information about the characteristics of the tissue.…”
Section: Discussionmentioning
confidence: 54%
“…30,31) In conclusion, based on the present study we propose that radiolabeled glycerol could be used as a molecular probe targeting agAQPs. This might enable the estimation of agAQP expression by comparing radioactivity in the tissue of interest and plasma in the same individual, thus providing valuable information about the characteristics of the tissue.…”
Section: Discussionmentioning
confidence: 54%
“…For example, recent PET research on liver metastases using 15 O-radiolabelled water has shown that those with higher plasma tissue perfusion variables (i.e. improved blood flow or perfusion) were associated with better patient RT outcome and improved survival [63][64][65]. This suggests that assessment of indicators of tumour perfusion, such as exchangeable tissue volume of distribution using PET, may be useful as BTV markers.…”
Section: Discussionmentioning
confidence: 99%
“…A 10% decrease in V T was also observed at this timepoint. Early phase [ 15 O]-water PET studies can be used to calculate both of these values, as both parameters can provide important information on the mechanism of action of experimental anti-cancer agents [15]. Two clinical studies have used [ 15 O]-water PET to assess the efficacy of anti-angiogenic agents.…”
Section: Pet Tracers For Measuring Tumour Vascular Physiology: [ 15 Omentioning
confidence: 99%